Next-generation sequencing yields the complete mitochondrial genome of the Lista haraldusalis (Walker, 1859). Issue 2 (2nd April 2020) - Shi, Yu-Xia; Song, Lu; Li, Jun-Hao; Su, Si-Lin; Tian, Yong-Ji; Li, Shu-Mei; Zhang, Hong-Fei; Ding, Wei-Li; Yang, Ming-Sheng
Abstract: In this study, complete mitochondrial genome of the Lista haraldusalis (Walker, 1859) is sequenced through next-generation sequencing method. The L. haraldusalis mitogenome is a circular, double-stranded molecule, with 15, 213 bp in length. The typical 37 mitochondrial genes (13 PCGs, 22 tRNAs, and 2 rRNAs) and an A + T-rich region are recognized. Gene content and arrangement are highly conserved and typical of Lepidoptera. Interestingly, in the intergenic region between trnN and trnS1, a microsatellite sequence of (TA)12 is recognized. Phylogenetic analysis based on the 13 PCGs plus two rRNAs sequences recovered that the Pyralidae and Crambidae are reciprocally monophyletic. The L. haraldusalis sequenced in this study is nested into the Pyralidae clade, reinforcing previous morphological and molecular studies.